Working performances of carrot root extraction machines - Sito, Stjepan (Array, 2019)
This paper presents results of field measurements of working performance and fuel consumption evaluation in various operating conditions. Three versions of carrot extraction machines (Dewulf, Europa 2000 and Asa lift) at three locations and two varieties of carrots (Maestro F1 and Mello Yello F1) was. In optimum soil conditions, fuel consumption ranged from 8.4 to 12.5 L/ha, while in heavy operation conditions for extraction machines fuel consumption increased significantly for 65%. The performance of carrot extraction in optimal soil conditions was on average between 3-4 t/ha. In unfavorable soil conditions (soil sodden, mud or too dry soil) working effects up to 70% and this has direct negative consequences on the overall carrots production costs.